Studi Produktivitas Air Aliran Batang Dan Lolosan Tajuk Pada Tegakan Mahang (Macaranga gigantea) Dan Bangkirai (Shorea laevis) Di Kebun Raya Unmul Samarinda, Kalimantan Timur. - munasirah, Munasirah; Hendra, Medi; Susanto, Dwi (BIOPROSPEK: Jurnal Ilmiah Biologi, 2018)
The purposes of experiments were to determine how many were total waters of steam flow and through fall on S. laevis trees and how many were the highest nutrient contentes of Nitrogen (N), Phosphor (P), Potassium (K), Calcium (Ca), and Magnesium (Mg) in rain waters of and S. laevis trees. The method used experiment was quantitative analysis which was done measurement directly in the field, the data consistes of tree height, steam diameter, canopy diameter, measurement waters of steam flow and through fall, nutrient contentes (N, P, K, Ca, and Mg). The result of an average totally of the highest steam flow and through fall was 6.850,00 ml in method 2. Although an average of the lowest steam flow was 33,33 ml in method 3 and an average of the lowest through fall was 3.275,83 ml in method 1. An average of the highest nutrient content N was 695 ppm in steam flow the averages of the highest nutrient contentes P and K were P= 4 ppm and K= 8.619 ppm in through fall, an average of the highest nutrient content Ca was 3 ppm in through fall and an average of the highest nutrient content Mg in through fall was 2 ppm in through fall.